VARIATION OF UTTERANCES USED IN CHILDREN FILMS MANUSCRIPT (PRAGMATICS APPROACH) - HUSNA, NISAUL (2007)
This study is aimed at describing the form and the function of utterances. The data are children utterances in the form of sentence that are taken from children films manuscript, titled Harry Potter and the Sorcerer’s Stone and Harry Potter and the Chamber of Secret. In collecting the data, the writer uses documentation method by selecting the children sentence utterances, which can be found in Harry Potter and the Sorcerer’s Stone and Harry Potter and the Chamber of Secret films manuscript. To achieve these objectives, she classifies the data based on sentence types to formulate the forms, and then she applies the speech act theory to judge the function. After analysing the data, the writer found the forms of children sentence uterances are declarative, interrogative, and imperative. Based on the form of declarative sentence, it can be classified into four (4): simple sentence, compound sentence, complex sentence, and compound-complex sentence. From each imperative sentence, she finds that not all imperatives are initiated by predicate. There are imperatives which is marked by the marker Let and Don’t. Based on the interrogative sentence, she finds most of them are initiated by question words like what, who, where, and how. Besides that the writer also finds that interrogative does not always intiated by auxiliary, modal, or question words but also a subject in the innitial position of sentence Related with the function, she found declarative not only has function as informing, interrogative as asking, and imperative as commanding. The variant function of declarative are exclamation, commanding, warning, requesting, and offering, interrogative has variant function to express requesting, and imperative has variant function to express requesting and warning.